2019
DOI: 10.1371/journal.pone.0211061
|View full text |Cite|
|
Sign up to set email alerts
|

Blast resistance in Indian rice landraces: Genetic dissection by gene specific markers

Abstract: Understanding of genetic diversity is important to explore existing gene in any crop breeding program. Most of the diversity preserved in the landraces which are well–known reservoirs of important traits for biotic and abiotic stresses. In the present study, the genetic diversity at twenty-four most significant blast resistance gene loci using twenty-eight gene specific markers were investigated in landraces originated from nine diverse rice ecologies of India. Based on phenotypic evaluation, landraces were cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
27
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 62 publications
5
27
0
1
Order By: Relevance
“…As expected, the studied markers showed, in general, low allelic diversity. Our results corroborate with the previous findings of Yadav et al (2019), who reported that the average number of alleles was two and the mean gene diversity was 32%. In the current study, among the 10 genotypes screened for the presence of major blast resistance genes, at least one genotype had one allele of the eight major R genes (Table 6).…”
Section: Genotype Identification and Allelic Diversitysupporting
confidence: 93%
See 1 more Smart Citation
“…As expected, the studied markers showed, in general, low allelic diversity. Our results corroborate with the previous findings of Yadav et al (2019), who reported that the average number of alleles was two and the mean gene diversity was 32%. In the current study, among the 10 genotypes screened for the presence of major blast resistance genes, at least one genotype had one allele of the eight major R genes (Table 6).…”
Section: Genotype Identification and Allelic Diversitysupporting
confidence: 93%
“…Additionally, four markers were identified in Sakha104, Sakha108, and Eg-N-3. The use of molecular markers for the identification of rice genotypes carrying resistance genes is well-established in different geographic regions (Liu et al, 2015;Zhang et al, 2015;Yadav et al, 2019); however, in Egypt and Saudi Arabia, research related to the identification of resistance genes in rice is still in preliminary stages.…”
Section: Genotype Identification and Allelic Diversitymentioning
confidence: 99%
“…In a more recent study, Yan et al (2017) reported the genetic frequencies of 11 R genes, ranging from 9.4 to 100.0% in 32 Chinese rice germplasms while Yadav et al (2019) reported the genetic frequencies ranged between 4.96 and 100.0% in 161 Indian rice landraces. Prior to this study, Hannum et al (2018) have screened 15 rice accessions originating from other districts in North Sumatra and reported higher genetic frequencies from 47.0 to 100.0%.…”
Section: Discussionmentioning
confidence: 99%
“…In another research article, molecular analysis of variance of landraces originated from nine diverse rice ecologies of India showed maximum (93%) diversity within the population and least (7%) between populations. Five markers like K3957, Pikh, Pi2-i, RM212and RM302 were strongly associated with blast disease with the phenotypic variance of 1.4% to 7.6% [190].…”
Section: Marker-based Breeding Methodsmentioning
confidence: 99%